Determination of Islamic Education Methods: Analysis of al-Qiṣah, al-Mau'iẓah, and al-Uswah al-Hasanah as Islamic Family Education Methods - Asrizal Saiin; Zaitun; Anwar M. Raadiamoda (Jurnal Pendidikan Islam Indonesia, 2022)
The purpose of this study is to express ideas and develop knowledge about appropriate Islamic education methods as the development of Islamic family education methods, especially referring to the Qur'an as the main source of the basics of Islamic education. The method used is descriptive qualitative method because this research is a library research type. Due to the nature of this research, the data are taken from written sources, such as books, journals, papers, and various scientific literatures whose authenticity can be accounted for. The result of this research is that there are three methods of Islamic education which are mentioned directly in the Qur'an, namely; 1) the story method (al-Qiṣah), 2) the advice method (al-Mau'iẓah), 3) the exemplary method (al-Uswah al-Hasanah), in which these methods can be used as a method of developing Islamic family education. However, in fact there are many other methods that can be used as methods of family education in Islam, but are not mentioned directly in the Qur'an as the three methods have been mentioned.